Retinoic Acid Signal Negatively Regulates Osteo/Odontogenic Differentiation of Dental Pulp Stem Cells - Jiangyi Wang; Guoqing Li; Lei Hu; Fei Yan; Bin Zhao; Xiaoshan Wu; Chunmei Zhang; Jinsong Wang; Juan Du; Songlin Wang (Stem Cells International)
Retinoic acid (RA) signal is involved in tooth development and osteogenic differentiation of mesenchymal stem cells (MSCs). Dental pulp stem cells (DPSCs) are one of the useful MSCs in tissue regeneration. However, the function of RA in osteo/odontogenic differentiation of DPSCs remains unclear. Here, we investigated the expression pattern of RA in miniature pig tooth germ and intervened in the RA signal during osteo/odontogenic differentiation of human DPSCs. Deciduous canine (DC) germs of miniature pigs were observed morphologically, and the expression patterns of RA were studied by in situ hybridization (ISH). Human DPSCs were isolated and cultured in osteogenic induction medium with or without RA or BMS 493, an inverse agonist of the pan-retinoic acid receptors (pan-RARs). Alkaline phosphatase (ALP) activity assays, alizarin red staining, quantitative calcium analysis, CCK8 assay, osteogenesis-related gene expression, and in vivo transplantation were conducted to determine the osteo/odontogenic differentiation potential and proliferation potential of DPSCs. We found that the expression of RARβ and CRABP2 decreased during crown calcification of DCs of miniature pigs. Activation of RA signal in vitro inhibited ALP activities and mineralization of human DPSCs and decreased the mRNA expression of ALP, osteocalcin, osteopontin, and a transcription factor, osterix. With BMS 493 treatment, the results were opposite. Interference in RA signal decreased the proliferation of DPSCs. In vivo transplantation experiments suggested that osteo/odontogenic differentiation potential of DPSCs was enhanced by inversing RA signal. Our results demonstrated that downregulation of RA signal promoted osteo/odontogenic differentiation of DPSCs and indicated a potential target pathway to improve tissue regeneration.